More Than a Job Club, Sister: Career Intervention for Women Following Incarceration. Issue 1 (March 2017) - Snodgrass, Jill L.; Jenkins, Betsy B.; Tate, Kelly F.
Abstract : Following incarceration, women face unique challenges in returning to their communities and seeking employment. This qualitative study used interpretative phenomenological analysis to explore the lived experiences of previously incarcerated women as they participated in It's More Than a Job Club, Sister, a spiritually integrated career intervention, and subsequently sought employment. The following 4 superordinate themes emerged describing this experience: (a) It was more than a job club; (b) God gave me a second chance: the impact of faith on recovery and employment; (c) barriers to employment; and (d) looking ahead. The findings indicate the need for a strengths‐based approach to career intervention that builds upon existing skills and emphasizes identity exploration, uncovering core beliefs and vocational values, bridging the gap between goals and barriers, and leveraging interpersonal skills. The findings also indicate that career counseling with female returning citizens is enhanced by incorporating attention to the role of substance abuse/recovery and by attending to the intersection of calling and vocation.